2019
DOI: 10.17559/tv-20170529143820
|View full text |Cite
|
Sign up to set email alerts
|

FEM Numerical Simulations of the Mechanical Clinching Process of HC260Y Steel

Abstract: This paper presents the results of FEM numerical simulations, of the HC260Y steelsheet mechanical clinching process. The starting tool parameters were chosen for the central composite design of experiments, in order to find out which tool parameters have the largest contribution to the sheet joint interlock. Assessment of the mathematical model, and analysis of variance (ANOVA) were performed within the design of experiments. This numerical analysis was done to find the most suitable tool geometry and tool wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Cumin et al [62] performed the FEM numerical simulations of the mechanical clinching process of the HC260Y steel sheet. The FEM results revealed that the clinching tool loads were obtained, along with the insight on how the interlock is formed and how the material flow is governed by the tool shape.…”
Section: Aluminum Alloy and Steelmentioning
confidence: 99%
“…Cumin et al [62] performed the FEM numerical simulations of the mechanical clinching process of the HC260Y steel sheet. The FEM results revealed that the clinching tool loads were obtained, along with the insight on how the interlock is formed and how the material flow is governed by the tool shape.…”
Section: Aluminum Alloy and Steelmentioning
confidence: 99%